2010
DOI: 10.1159/000313816
|View full text |Cite
|
Sign up to set email alerts
|

Oxane HD and Retinal Detachment Surgery in Routine Clinical Practice

Abstract: Background/Aims: To assess the outcomes and complications of endotamponade with Oxane HD following retinal detachment repair. Methods: Retrospective consecutive case series of inferior retinal detachment with Oxane HD endotamponade within a 3-year period. Results: Case notes for 18 eyes of 18 patients were reviewed. Four (22.2%) were total retinal detachments and 13 (72.2%) had proliferative vitreoretinopathy. The mean Oxane HD endotamponade and follow-up durations were 27 ± 38 and 66 ± 39 weeks, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…Clinical studies have shown the early emulsification of these HSOs. 12,18,19 The heavy additives are not viscous in nature, and therefore they are suspected of causing the early emulsification. The 11% silica fluid has a different design than either Desiron 68 or Oxane HD.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown the early emulsification of these HSOs. 12,18,19 The heavy additives are not viscous in nature, and therefore they are suspected of causing the early emulsification. The 11% silica fluid has a different design than either Desiron 68 or Oxane HD.…”
Section: Discussionmentioning
confidence: 99%
“…The same applies to the description of silicone as "oil". all studies with only 1 exception (mean: 27 weeks [1]). Permanent anatomic success was achieved in 70% of treated eyes (range: 54 -89) without further interventions, except removal of Oxane HD.…”
Section: F6 H8mentioning
confidence: 98%
“…It was the first heavi-er-than-water internal tamponade approved for clinical use (up to 3 months). In addition to a 3-center approval study [15] there are 3 study reports (4 publications, [8,23,25]) 1 with at least 10 eyes in each case series available, altogether including only 72 eyes. F 6 H8 was used in these studies as internal tamponade mainly for short periods of 3.5 to 10 weeks.…”
Section: F6 H8mentioning
confidence: 99%
See 2 more Smart Citations